Screening of Wild Strawberry Germplasm for Iron-deficiency Tolerance Under Hydroponic Conditions - Sedat Serçe; Nazife Erdem; Yıldız Aka Kaçar; M. Bülent Torun; Ayfer Alkan Torun (Journal of Agricultural Sciences, 2022)
Cultivated strawberry has been developed from hybridization between Fragaria chiloensis and F. virginiana. The progenitor species exhibit significant genetic diversity. Growth attributes of progenitor species and their responses to several stress factors have been studied. However, iron-deficiency tolerance (FeDT) of different species have merely been tested under hydroponic conditions. This study evaluated FeDT of 23 genotypes belonging to super-seed collection under hydroponic conditions. Two genotypes (one Fe-deficiency tolerant and one sensitive) were selected from screening experiment and their physiological and morphological mechanisms playing role in FeDT were determined. Plant parameters associated with FeDT, i.e., pH of the growth medium, root Fe reductase activity, total and active Fe concentration of shoot were recorded. The Fe-efficiency of strawberry subspecies varied between 51% and 98%. Fe efficiency values also varied among subspecies. AukeLake and RCP37 belonging to F. chiloensis were highly resistant and sensitive to Fe-deficiency, respectively based on Fe efficiency values. A highly significant relationship was observed between Fe concentration and FeDT of the genotypes. Acidification of nutrient solution and root Fe reductase activity were closely related to high shoot iron concentration. Our findings indicated existence of a close relationship between root uptake and root to shoot translocation of Fe, which ultimately contribute greatly to FeDT among tested strawberry genotypes.